Interleukin‐1 Blockade Inhibits the Acute Inflammatory Response in Patients With ST‐Segment–Elevation Myocardial Infarction. Issue 5 (3rd March 2020) - Abbate, Antonio; Trankle, Cory R.; Buckley, Leo F.; Lipinski, Michael J.; Appleton, Darryn; Kadariya, Dinesh; Canada, Justin M.; Carbone, Salvatore; Roberts, Charlotte S.; Abouzaki, Nayef; Melchior, Ryan; Christopher, Sanah; et al.
Abstract : Background: ST‐segment–elevation myocardial infarction is associated with an intense acute inflammatory response and risk of heart failure. We tested whether interleukin‐1 blockade with anakinra significantly reduced the area under the curve for hsCRP (high sensitivity C‐reactive protein) levels during the first 14 days in patients with ST‐segment–elevation myocardial infarction (VCUART3 [Virginia Commonwealth University Anakinra Remodeling Trial 3]). Methods and Results: We conducted a randomized, placebo‐controlled, double‐blind, clinical trial in 99 patients with ST‐segment–elevation myocardial infarction in which patients were assigned to 2 weeks treatment with anakinra once daily (N=33), anakinra twice daily (N=31), or placebo (N=35). hsCRP area under the curve was significantly lower in patients receiving anakinra versus placebo (median, 67 [interquartile range, 39–120] versus 214 [interquartile range, 131–394] mg·day/L; P <0.001), without significant differences between the anakinra arms. No significant differences were found between anakinra and placebo groups in the interval changes in left ventricular end‐systolic volume (median, 1.4 [interquartile range, −9.8 to 9.8] versus −3.9 [interquartile range, −15.4 to 1.4] mL; P =0.21) or left ventricular ejection fraction (median, 3.9% [interquartile range, −1.6% to 10.2%] versus 2.7% [interquartile range, −1.8% to 9.3%]; P =0.61) at 12 months. The incidence of death or new‐onset heart failure or of death and hospitalization for heart failure was significantly lower with anakinra versus placebo (9.4% versus 25.7% [ P =0.046] and 0% versus 11.4% [ P =0.011], respectively), without difference between the anakinra arms. The incidence of serious infection was not different between anakinra and placebo groups (14% versus 14%; P =0.98). Injection site reactions occurred more frequently in patients receiving anakinra (22%) versus placebo (3%; P =0.016). Conclusions: In patients presenting with ST‐segment–elevation myocardial infarction, interleukin‐1 blockade with anakinra significantly reduces the systemic inflammatory response compared with placebo. Clinical Trial Registration: URL: https://www.clinicaltrials.gov/ . Unique identifier: NCT01950299.